Carbon accounting system: the bridge between carbon governance and carbon performance in Malaysian Companies - Tze San Ong (Taylor & Francis Group, 2021)
Introduction:Research has shown the negative impacts of climate change on the economy and how the state of the environment has been a complex global challenge. Prior studies have suggested immediate actions to avoid any unforeseen circumstances for all living things on Earth. Previous research has also supported all kinds of sustainability efforts as resolutions to address the deterioration of climate change caused by business activities. Originality: There is a need for companies to start acting and assigning employees to mitigate carbon emitted by corporations. This study is motivated by the lack of empirical evidence that examines how corporate carbon governance influences better carbon performance of organizations and authorizes organizations to implement and embed carbon accounting. Objective: This study used evidence from Malaysia to explore this subject matter and examined the association between carbon governance and carbon performance of corporations. The research also investigated the mediation effect of carbon accounting with respect to carbon governance and carbon performance. Findings: It is revealed that carbon governance had no significant influence on an organization’s carbon performance although carbon accounting implementation positively influenced carbon performance. The findings imply that despite its insignificance, carbon accounting remains a vital matter to be deployed by organizations for better carbon emission mitigation.